2011
DOI: 10.1007/s11010-011-1098-5
|View full text |Cite
|
Sign up to set email alerts
|

Genetic association of Glutathione peroxidase-1 (GPx-1) and NAD(P)H:Quinone Oxidoreductase 1(NQO1) variants and their association of CAD in patients with type-2 diabetes

Abstract: Coronary artery disease (CAD) is a major health concern and the leading cause of death in individuals with type-2 diabetes mellitus (T2DM). Glutathione peroxidase-1 (GPx-1) and NAD(P)H: quinone oxidoreductase (NQO1) are known for its broad range of detoxification. The role of functional variants of these genes in the development of various disorders is proven. Hereby, we investigated the possible role of these variants in the development of CAD in T2DM patients of South Indian population. In this case-control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
32
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 44 publications
2
32
0
Order By: Relevance
“…In addition to its well‐known antioxidant properties [reviewed in (Ross & Siegel, 2017)], NQO1 exerts significant metabolic functions by conferring protection against obesity, hypertension, arterial restenosis, renal injury, and neurodegenerative disorders (Chhetri, King & Gueven, 2017; Hwang et al., 2009; Kim et al., 2011; Son et al., 2015). The C609T (Pro187Ser) null polymorphism of the NQO1 gene is associated with increased risk of complications related to metabolic syndrome, Alzheimer's disease, and an overall increased risk of cancer in humans (Chhetri et al., 2017; Lajin & Alachkar, 2013; Martinez‐Hernandez et al., 2015; Ramprasath et al., 2012). Genetic ablation of NQO1 in rodent models also increases sensitivity to skin carcinogenesis (Iskander et al., 2005) and causes severe dysregulation of lipid and glucose metabolism (Gaikwad, Long, Stringer & Jaiswal, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to its well‐known antioxidant properties [reviewed in (Ross & Siegel, 2017)], NQO1 exerts significant metabolic functions by conferring protection against obesity, hypertension, arterial restenosis, renal injury, and neurodegenerative disorders (Chhetri, King & Gueven, 2017; Hwang et al., 2009; Kim et al., 2011; Son et al., 2015). The C609T (Pro187Ser) null polymorphism of the NQO1 gene is associated with increased risk of complications related to metabolic syndrome, Alzheimer's disease, and an overall increased risk of cancer in humans (Chhetri et al., 2017; Lajin & Alachkar, 2013; Martinez‐Hernandez et al., 2015; Ramprasath et al., 2012). Genetic ablation of NQO1 in rodent models also increases sensitivity to skin carcinogenesis (Iskander et al., 2005) and causes severe dysregulation of lipid and glucose metabolism (Gaikwad, Long, Stringer & Jaiswal, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Despite low GPX1 and SOD1 activities in islets (only 2% and 29% of that in liver, respectively) (39), we have found that knockout of GPX1 (GPX1 knockout [GKO]) and SOD1 (SOD1 knockout [SKO]) alone or in combination (double knockout of GPX1 and SOD1 [dKO]) caused substantial impairment of GSIS (68). Consistently, a Gpx1 gene variant (C198T) lowering the enzyme activity was identified in the South Indian population, which resulted in increased incidences of type 2 diabetes (C/T, 1.4-fold and T/T, 1.8-fold) (54). Intriguingly, the overt phenotypes of GSIS impairments in the GKO and SKO mice were similar (68), although GPX1 catalyzes H 2 O 2 breakdown whereas SOD1 catalyzes H 2 O 2 formation.…”
Section: Introductionmentioning
confidence: 99%
“…Shohrati et al demonstrated that SM injured patients with higher severity of injuries had lower levels of glutathione than those with mild injuries (44). In addition, it was shown that glutathione peroxidase can be associated with CAD (45).…”
Section: Biochemical and Laboratory Findingsmentioning
confidence: 99%
“…In addition, the mentioned molecules and mediators play a remarkable role in cardiovascular disorders, such as endothelial injuries secondary to reactive oxygen species and toxins (9,45,53). Although the inflammatory process is carried out in airway leaking, even small amounts of these mediators within the systemic circulation can affect other organs.…”
mentioning
confidence: 99%
See 1 more Smart Citation